Environmental and social implications of integrated seawater agriculture systems producing Salicornia bigelovii for biofuel. Issue 5 (September 2012) - Bailis, Rob; Yu, Elaine
Background: This article examines environmental and social sustainability of integrated seawater agriculture systems growing Salicornia bigelovii for biofuel. Case studies in Eritrea and Mexico are evaluated using Roundtable on Sustainable Biofuels criteria.Results: Producer claims versus accomplishments centered on desirable environmental and socioeconomic outcomes are discussed. Operations ceased due to political instability, mismanagement and community opposition.Conclusion: Dialogue promoting sustainable biofuel suggests producers utilize marginal land; however, marginal land may contain sites of ecological or cultural significance. Implementation efforts, however well intentioned, may involve tradeoffs and political maneuvering that can derail projects. In these case studies, conflicting narratives and limited transparency further compounded technical and social complexity. Free, prior and informed consent as well as independent environmental monitoring could reduce risk of project failure.